Strategi Kepala Madrasah dalam Peningkatan Kompetensi Tenaga Pendidik dan Kependidikan di Madrasah Tsanawiyah - Sa'adah, Nur Lailatus (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
The head of the madrasa is the leader of educational institutions responsible for the management of educational institutions such as educational activities, madrasa administration, fostering teaching and education staff, and utilization and maintenance of facilities and infrastructure. The purpose of this study is to find out and describe: in increasing the competence of educators and education staff, 2) The process of implementing the principal's strategy in improving the competence of educators and education staff. 3) The implications of implementing the program enhance the competence of educators and education staff. This type of research is qualitative research with a descriptive approach. For data collection techniques, researchers conduct interviews, documentation and direct observation. Meanwhile, to confirm, researchers used data triangulation techniques. The results found by researchers in the field are: 1) The strategy process carried out by the head of the madrasah by observing the needs of educators and education, planning the implementation of the program, evaluating the planned program, 2) The process of implementing the program, namely the head of the madrasa prepares a program in the form of seminars, workshops, training, technical guidance and training in the workplace, 3) Impacts obtained by program participants are increased knowledge, increased skills possessed and having connections outside of educational institutions.